Nvos (Networked Virtual Organisations) and Other Forms of Networks Small and Medium-Sized Enterprises in the Web of New Cooperation Forms - Noszkay, Erzsébet (Theory, Methodology, Practice – Review of Business and Management, 2007)
The so called association-based systems are not new-fangled ideas; they have long been known in various economies. Nowadays network-forming is mentioned as a way of successful innovation, moreover, it is often assigned as a crucial condition of staying on the market. Although Hungarian journals have attempted to draw a picture of the benefits of networks for SMEs - as “appetisers” based on the examples of developed market economies - since the 1990s, the interest of Hungarian entrepreneurs has been rather meagre. However, this situation seems to be changing slightly. The indifference of SMEs, especially in the knowledge-based sectors has now been replaced by perceptible interest. This article – focusing on the latter circle of enterprises – seeks to answer the following questions: What are the realisations and typical motives of the recent interest of SMEs in forming networks? What are the main goals and advantages of forming networks for SMEs in Hungary? What type of networks would be the most efficient for this circle (considering the characteristics of domestic enterprises)? What are the most effective tools and solutions assisting SMEs in becoming acquainted with modern networks and joining them adequately?